Maternal risk factors for neonatal asphyxia in severe pre-eclampsia: study at the University Hospital of Obstetrics and Gynecology, Befelatanana - Ranjandriarison, Dorland T.; Rakotondraibe, Aurelien M.; Randriamahavonjy, Romuald; Randriambelomanana, Joseph A.; Andrianampanalinarivo, Hery R. (International Journal of Research in Medical Sciences, 2026)
Background: Severe pre-eclampsia remains a major cause of perinatal morbidity and mortality. Neonatal asphyxia is one of its most serious complications. This study aimed to identify maternal factors associated with neonatal asphyxia in cases of severe pre-eclampsia. Methods: A retrospective analytical case–control study was conducted at the University Hospital Center of Obstetrics and Gynecology Befelatanana over a 13-month period (January 2020-January 2021). Cases were newborns with an Apgar score ≤7 at 5 minutes or absence of immediate cry. Controls were vigorous newborns with an Apgar score of 10 at 5 minutes. A 1:2 sampling ratio was used. Data were analyzed with Epi-Info™ 7.2.5.0. Associations were expressed using odd ratios (OR) with 95% confidence intervals. Results: Among 6,252 live births, 105 cases of severe pre-eclampsia were recorded, including 35 newborns with neonatal asphyxia (33.33%). The strongest risk factors were gestational age <37 weeks (OR 48.07; p=7.3×10⁻⁹), low birth weight <2500 g (OR 21.80; p=5.6×10⁻⁹), maternal convulsive crisis (OR 10.69; p=1.8×10⁻⁶), elevated serum creatinine ≥120 µmol/L (OR 25.5; p=4.96×10⁻⁷), vaginal bleeding (OR 20.44; p=0.00057), and severe hypertensive symptoms (OR 4.14; p=0.0025). Referral admission also increased the risk (OR 3.22; p=0.016). Conclusions: Neonatal asphyxia in severe pre-eclampsia is strongly associated with prematurity, low birth weight, maternal complications, organ dysfunction, and delayed referral. Early recognition, improved antenatal surveillance, timely maternal stabilisation, and effective referral systems are essential to reduce neonatal morbidity and mortality.